Influence of AI in HR Skill Optimizing - Sheshadri, Sandhya (Global journal of Business and Integral Security, 2023)
n today's rapidly evolving global economy, Human Resources (HR) departments face intricate challenges in ensuring employee satisfaction, enhancing productivity, and retaining top talent within a dispersed workforce. The integration of Artificial Intelligence (AI) offers a paradigm shift in addressing these challenges, empowering HR professionals with advanced tools for data-driven decision-making. This thesis explores the multifaceted collaboration between AI and HR, delving into its transformative applications across various domains. By seamlessly integrating AI algorithms, HR departments can optimize talent acquisition processes, efficiently match candidates with job requirements, and eliminate biases inherent in traditional recruitment methods. Moreover, this study investigates the innovative potential of AI in mapping collaboration networks within organizations. Through network analysis techniques, such as those facilitated by Network, HR practitioners can uncover hidden patterns of interaction beyond conventional hierarchies. This insight fuels the development of tailored strategies for team building, communication enhancement, and cross-functional collaboration. The research further illuminates the capacity of AI to revolutionise training recommendations. By harnessing user-item recommendation techniques, empowered by deep learning and word embeddings, HR professionals can deliver personalized training pathways to employees. This not only bridges skill gaps but also cultivates a culture of continuous learning, fostering individual growth and organizational agility. Additionally, the research delves into AI's potential in predicting employee attrition, a critical concern for HR departments. Through sophisticated classification models, bolstered by deep learning frameworks like Keras and TensorFlow, AI can analyse historical and real-time data to foresee attrition trends. This foresight enables HR to adopt proactive retention strategies, optimising workforce stability and maintaining organizational resilience. Ethical considerations loom large as AI permeates HR practices. In summation, this thesis unveils a dynamic convergence of AI and HR, reshaping the contours of employee management. Through comprehensive exploration and insightful analysis, this study illuminates the transformative potential of AI across talent acquisition, collaboration enhancement, training recommendations, and attrition prediction, while underscoring the ethical imperatives that should guide its implementation.